Composition and petrology of a mush-bearing magma reservoir beneath Tenerife - Horn, EL; Taylor, RN; Gernon, TM; Stock, MJ; Farley, EMR (Oxford University Press, 2022)
Deciphering the dynamics of sub-volcanic magmatic processes requires a detailed understanding of the compositional and textural relationships between melt and crystals. To examine these relationships, we investigated material from one of the largest caldera-forming explosive eruptions on the ocean island of Tenerife, the 312-ka Fasnia event. This eruption ejected juvenile pyroclasts of melt-bearing, partially crystalline cumulate nodules alongside phonolitic pumice and accidental lithic clasts. Nodules contain an average of 26% melt that is preserved as vesiculated and microcrystalline basanite in segregations, pathways and interstitial domains. Both the microcrystalline groundmass and crystal framework are generally unaltered as this crystal ‘mush’ remained supra-solidus until the eruption. We find no surficial or intrinsic evidence that the nodules were transported from their reservoir in a ‘carrier’ magma, and it is most likely that the mush was in situ when it was explosively fragmented and ejected during eruption. As such, the nodules preserve a record of the proportions and relationships between the crystal framework and pre-eruptive melt in an active magma mush reservoir, importantly, capturing a snapshot of the sub-volcanic system at a single point in time. We have analysed >100 of the mush nodules from the massive lithic breccia facies within the Fasnia Member of the Diego Hernández Formation. These cumulates span a diverse range of alkaline plutonic lithologies, from wehrlite and pyroxenite, through hornblende gabbros, to monzodiorite and syenite. Their textures record a range of crystallization environments, including both crystal- and melt-rich groundmass domains, and invasion of near-solidus domains by ascending reactive melts. In addition, the cumulus phases record complex interactions between felsic and mafic magmas throughout their development, providing evidence for mush remobilization and disequilibrium. Relative homogeneity of melt compositions through the mafic and felsic lithologies testifies to melt mobility through the cumulates. Nevertheless, all melts are of different basanite-intermediate composition to the juvenile phonolitic pumice ejected during the same eruption. This observation implies that the mafic–felsic cumulate mush and the phonolite did not experience significant two-way mixing and existed as separate crustal reservoirs. However, the Fasnia eruption simultaneously fragmented and removed material from both reservoirs, implying the mafic system was subjacent to the felsic, but they did not form a contiguous body.